In Lampadem mundani splendoris acceditur - Joanna Komorowska
The article proposes the reading of Capella’s NMPh I 14–15 and the relevant encounter of Mercury and Apollo against the background of contemporary astrological doctrine. The carefully outlined astrological semantics of the seven rivers and of the subsequent rising of Apollo/the Sun provide an additional insight into the complex and multilayered nature of Mercury’s travels as portrayed by Martianus, but also furnish an important indication of the overall importance of the astrological component in the work.